Analysis An Intention to Use Electronic Wallet during Covid-19 Pandemic - Indrian Kusuma, Gabriel Boggie; Dirgantara, I Made Bayu (Universitas Negeri Semarang, 2021)
The number of Covid-19 spread is increasing in several countries, including Indonesia. The situation encourages World Health Organization (WHO) with local government authorities implement various policies, such as physical distancing and stay at home. Interestingly, this policy inspires consumers to carry out contactless activities, especially in making payment transactions. The purpose of study was to analyze the factors which influence the adoption of E-wallet during Covid-19 pandemic. To analyze the adoption behavior of using E-wallet, a conceptual framework is proposed based on the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use Technology (UTAUT). Data was collected in the form of an online questionnaire which was distributed to 150 respondents using purposive sampling technique and tested using the AMOS 22 Structural Equation Modeling (SEM) Approach. The results showed that Personal Innovation, Experience, Social Influence had a significant effect on Intention to Use E-wallet through Perceived Ease Of Use and Perceived Usefulness.